Determinan Minat Pelaku Ritel Menggunakan Quick Response Code Indonesian Standard (QRIS) sebagai Sistem Pembayaran Digital - Astuti, Zahratul Gina; Mariadi, Yusli (SAFE-Network, 2024)
The aim of this study is to examine and analyze the factors influencing retailers' interest in using QRIS as a digital payment system. The research employed a quantitative descriptive method. Primary data was gathered through the distribution of a Likert-scale questionnaire to a population of 20 members. Sample selection was drawn from the entire population. Subsequently, SmartPLS 3.0 software was utilized for data analysis. The research involved testing validity and reliability, model fit (Goodness of Fit), and hypothesis testing. The findings indicate that knowledge, perceived ease of use, perceived benefits, and perceived risks do not significantly affect retailers' interest in using QRIS. However, collectively, knowledge, perceived ease of use, perceived benefits, and perceived risks positively and significantly influence interest in using QRIS, explaining 57.4% of the variance, while the remaining 42.6% is influenced by other unexamined factors in this study.